sTWEAK as Predictor of Stroke Recurrence in Ischemic Stroke Patients Treated With Reperfusion Therapies - Hervella, Pablo; Pérez-Mato, María; Rodríguez-Yáñez, Manuel; López-Dequidt, Iria; Pumar, José M.; Sobrino, Tomás; Campos, Francisco; Castillo, José; da Silva-Candal, Andrés; Iglesias-Rey, Ramón (Frontiers in Neurology, 2021)
Aim: The purpose of this study was to investigate clinical and neuroimaging factors associated with stroke recurrence in reperfused ischemic stroke patients, as well as the influence of specific biomarkers of inflammation and endothelial dysfunction. Methods: We conducted a retrospective analysis on a prospectively registered database. Of the 875 patients eligible for this study (53.9% males; mean age 69.611.8 years vs. 46.1% females; mean age 74.912.6 years), 710 underwent systemic thrombolysis, 87 thrombectomy and in 78, systemic or intra-arterial thrombolysis together with thrombectomy was applied. Plasma levels of interleukin 6 (IL-6) and tumor necrosis factor alpha (TNFα) were analyzed as markers of inflammation, and soluble tumor necrosis factor-like inducer of apoptosis (sTWEAK) as an endothelial dysfunction marker. The main outcome variables of the study were the presence and severity of leukoaraiosis (LA) and stroke recurrence. Results: The average follow-up time of the study was 2513 months, during which 127 patients (14.5%) showed stroke recurrence. The presence and severity of LA was more severe in the second stroke episode (Grade III of the Fazekas 28.3% vs. 52.8%; p<0.0001). IL-6 levels at the first admission and before reperfusion treatment in patients with and without subsequent recurrence were similar (9.910.4 vs. 9.17.0 pg/ml, p=0.439), but different for TNFα (14.75.6 vs. 15.95.7 pg/ml, p=0.031) and sTWEAK (5,970.84,330.4 vs. 8,660.75,119.0 pg/ml, p<0.0001). sTWEAK values ≥7,000 pg/ml determined in the first stroke were independently associated to recurrence (OR 2.79; CI 95%: 1.87- 4.16, p<0.0001). Conclusions: The severity and the progression of LA are the main neuroimaging factors associated with stroke recurrence. Likewise, sTWEAK levels were independently associated to stroke recurrence, so further studies are necessary to investigate sTWEAK as a therapeutic target.